LIMITING THE NUMBER OF POLYGAMIES TO REALIZE ECONOMIC JUSTICE: A HERMENEUTIC ANALYSIS OF MUHAMMAD SYAHRUR - Saprudin, Udin; Junaedi, J; Kerwanto, K; Anurogo, Dito (QiST: Journal of Quran and Tafseer Studies, 2023)
Looking at the times, humanitarian problems have developed so complex, ranging from genetics, space exploration, education, interfaith relations, gender issues, human rights, and so on. The rapid development of the times makes Islamic sciences inevitably have to follow the flow of the times, and without exception the science of interpretation. The science of interpretation is required to always develop in the face of the complexity of humanitarian problems. It was here that the idea of the use of hermeneutics became a necessity for today's interpreters. Hermeneutics as a methodology in the interpretation of the Quran is considered quite important and urgent to do because hermeneutics does not only speak at the level of the text alone but also considers the context and role of subjectivity of an interpreter, so that by using the method of hermeneutics, interpretation or study of the Quran is expected to be able to become an actual contextual and answer the challenges of the times. The problem in this study is how Muhammad Syahrul's hermeneutic method in interpreting Quranic verses about Polygamy. The purpose of the study was to know and analyse Muhammad Shahrur's hermeneutics in interpreting Qur'anic verses about polygamy. The research method used in writing this paper is a qualitative research method through library research or literature review method using descriptive analysis writing method. The results showed that using his Limit Theory (Nadzariyah al-Hudud), Syahrur tried to reconstruct the understanding of polygamy by using quantity and quality standards together. In terms of quantity, the minimum standard limit for a person to marry is once (one wife), and the maximum limit is four wives. Islam allows a person to marry 4 (four) people together (polygamy), but in quality it is necessary to distinguish between the status of the first wife and the status of the second, third and fourth wives. For first wives (first marriages) one can marry a woman who is a virgin or widow whether or not she has children, but in a second, third, and/or fourth marriage (polygamy), the wife must be widowed and have orphans. So one cannot marry all one's wives in virgin condition, but on the contrary it is quite possible one marries wives who are all widows. This is in accordance with the main purpose of polygamy, which is to provide protection and protection and ensure the welfare and happiness of orphans living in intact families so as not to become homeless and avoid juvenile delinquency.